Peran Program Imtaq dalam Membentuk Karakter Siswa di SDI Ihsan Al-Bayti Terentem Kecamatan Janapria - Zakaki (Al-Faiza : Journal of Islamic Education Studies, 2024)
Character is an essential and fundamental thing in life. Not only that, the character is also like a living gem that distinguishes humans from animals. This study was conducted with the aim of 1) to determine the role of the imtaq program in shaping the character of students at SDI Ihsan Al-Baity 2) to determine the efforts to shape the character of students at SDI Ihsan Al-Baity 3) to determine the impact of imtaq program activities in shaping the character of students at SDI Ihsan Al-Baity. This type of research is qualitative descriptive. The data collection technique uses observation, interview, and documentation methods. Based on the data analysis, it can be explained that the Imtaq program's role in shaping students' character at the Islamic elementary school Ihsan Al-Baity has been carried out well. There are several roles of the imtaq program, including 1) increasing faith and devotion to God Almighty; 2) developing religious values; 3) increasing students' awareness to do good and avoid doing bad; 4) developing an attitude of responsibility, discipline, and independence; 5) increasing students' ability to adapt to the environment; 6) increasing spiritual intelligence; 7) developing students' tolerance. Second, efforts to form students' character at SDI Ihsan Al-baity through the imtaq program which is carried out in the morning by reading sholawat nahdatin, reading surah yasin, reading asmaul husna, memorizing prayers, memorizing hadith, practicing adzan, practicing iqomah, practicing prayer and studies by the imtaq instructor. Third, the impact of the image program in forming students' character at SDI Ihsan Al-baity is: students have religious morals, students have a responsible attitude, students begin to behave politely and courteously towards teachers and each other, students begin to obey school rules, often do good deeds, keep their promises and begin to help each other.